HUBUNGAN MOTIVASI DAN PERILAKU DENGAN TINGKAT PARTISIPASI PEREMPUAN PADA PROGRAM PEKARANGAN PANGAN LESTARI (Suatu Kasus pada Kecamatan Curug Kota Serang Provinsi Banten) - Azkiah Fikra; Ari Tresna Sumantri; Sri Mulyati; Aris Supriyo Wibowo; Sulaeni Sulaeni (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2022)
This study aims to determine the participation level of women farmers, analyze the relation between motivation and behavior with the participation level of women farmers in the P2L program. This research was conducted in the district of Curug Serang City, starting in May – June 2021. This type of research used a quantitative approach with a survey method. The sampling technique used was the saturated sampling method with 52 people as the sample population. The data used are primary and secondary data. In this study, the data were analyzed using descriptive analysis and spearman rank correlation test. The result showed the level of women farmers participation in Curug District in the program P2L which is considered quite active. Based on result rank spearman correlation test showed that there is a significant and positive relation between motivation with the level of participation has a moderate correlation strength, and there is a significant and positive relation between behavior with the level of participation has a moderate correlation strength.